Serum Renin Levels Increase With Age in Boys Resulting in Higher Renin Levels in Young Men Compared to Young Women, and Soluble Angiotensin-Converting Enzyme 2 Correlates With Renin and Body Mass Index - Jehpsson, Lars; Sun, Jiangming; Nilsson, Peter M.; Edsfeldt, Andreas; Swärd, Per (Frontiers in Physiology, 2021)
Background: Age, sex and body constitution may affect the shedding of membrane bound angiotensin-converting enzyme 2 (mACE2) and lead to a relative mACE2 deficiency. However, it is unclear if differences, reflected by serum renin levels, exist in the basal renin-angiotensin-system (RAS) between children and adults, boys and girls as well as young women and young men. Furthermore, it remains to be investigated if renin and soluble ACE2 (sACE2) levels are correlated with body mass index (BMI) in children and young adults. The aim of this observational study was to assess age-and sex differences in serum renin, and the relationship between renin, soluble angiotensin-converting enzyme 2 and body mass index in a prospectively followed population-based cohort of children which were followed into young adulthood. Study design: We analyzed renin and sACE2 in serum in a prospectively followed population-based cohort at 9.9 (0.6) [mean (SD)] (n=173), 11.7 (0.6) (n=156), 14.8 (0.8) (n=149), 18.8 (0.3) (n=93), and 23.5 (0.7) (n=152) years of age. Height (cm) and weight (kg) was measured and body mass index (BMI) was calculated as weight (kg)/height (m)2. Sex-related differences in renin levels were calculated using analysis of covariance, adjusted for age. Correlations were assessed by calculating the correlation coefficient (R2) using a multivariable linear mixed model. Results: Both sexes had low renin levels up to twelve years of age. Thereafter renin levels increased more in boys than in girls. Males from the age of 15 had significantly higher levels than females (p<0.001). There was a positive linear relationship between renin and sACE2 levels in male and female subjects (p<0.001), and between sACE2 levels and BMI in males (p<0.001). Conclusion: Renin levels increase with age, are higher in men than in women since around puberty, and are correlated with sACE2 levels. Furthermore, sACE2 levels are correlated with body mass index in males. These findings indicate that high renin levels in males and females and a high BMI in males may activate pathways which increase the shedding of mACE2, with possible implications for the risk of severe coronavirus disease 2019.